2023
DOI: 10.1128/aac.01315-22
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Mutational Spectrum of SARS-CoV-2 Replicating in the Presence of Ribavirin

Abstract: We report that ribavirin exerts an inhibitory and mutagenic activity on SARS-CoV-2-infecting Vero cells, with a therapeutic index higher than 10. Deep sequencing analysis of the mutant spectrum of SARS-CoV-2 replicating in the absence or presence of ribavirin indicated an increase in the number of mutations, but not in deletions, and modification of diversity indices, expected from a mutagenic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 92 publications
2
14
0
Order By: Relevance
“…However, the only bias that reached statistical significance was the presence of a G at the 5 0 side of A ! G transitions in populations treated with RBV, a preference that was previously reported (Somovilla et al, 2023). Mutational site biases appear to have played a minor role in the synergy between RDV and RBV for SARS-CoV-2.…”
Section: Increase Of Sars-cov-2 Mutational Load Upon Replication Of S...supporting
confidence: 73%
See 1 more Smart Citation
“…However, the only bias that reached statistical significance was the presence of a G at the 5 0 side of A ! G transitions in populations treated with RBV, a preference that was previously reported (Somovilla et al, 2023). Mutational site biases appear to have played a minor role in the synergy between RDV and RBV for SARS-CoV-2.…”
Section: Increase Of Sars-cov-2 Mutational Load Upon Replication Of S...supporting
confidence: 73%
“…• Their synergistic activity can extinguish the virus. Beaucourt & Vignuzzi, 2014;Brady et al, 2022;Geraghty et al, 2021;Somovilla et al, 2023). As a step towards searching for repositioned drugs that could suppress SARS-CoV-2, we have explored whether the activity of RBV against SARS-CoV-2 could be reinforced by the inhibition exerted by remdesivir…”
Section: What Does This Study Addmentioning
confidence: 99%
“…Several studies have shown that RBV inhibits the replication of SARS-CoV in vitro [ 25 , 26 , 27 ]. However, other studies have found that RBV does not exert any effect on virus replication in vivo [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…With this isolate, we have recently documented the synergistic antiviral activity exerted by the nucleoside analogs Rdv and Rib in cell culture (García-Crespo et al, 2024). Rib and, to a lesser extent, Rdv increased the mutation frequency of SARS-CoV-2 (Somovilla et al, 2023;García-Crespo et al, 2024). In that prior study, we reported the mutant spectrum composition of residues 22,872-23,645 (also with a mutation and deletion frequency cutoff of 0.1%) of 11 populations of USA-WA1/2020.…”
Section: Discordant Amino Acids and Deletions In Laboratory Preparati...mentioning
confidence: 99%
“…The laboratory populations analyzed resulted from infection of Vero E6 by SARS-CoV-2 USA-WA1/2020 (NCBI reference sequence NR-52281_70036318) (clade 19B) at a multiplicity of infection of 0.001 PFU/cell (monolayers of 2 × 10 5 -1 × 10 6 Vero E6 cells) as part of our ongoing project on lethal mutagenesis of SARS-CoV-2. The infections were carried out either in absence of drugs or in the presence of Rdv (5 μM or 10 μM) alone, Rib (100 μM or 150 μM) alone, or combinations of the two drugs (Rdv 2.5 μM or 5 μM; Rib 80 μM or 100 μM); the duration of the infection was 48 h. Drug concentrations were chosen according to their CC 50 and EC 50 values, to allow the presence of sufficient viral RNA for ultra-deep sequencing analysis (Somovilla et al, 2023;García-Crespo et al, 2024). All passage series in the absence and presence of drugs and all titrations for virus quantifications were carried out in triplicate (García-Crespo et al, 2024).…”
Section: Sars-cov-2 Patient Samples Laboratory Populations and Infect...mentioning
confidence: 99%